PENGADAAN TANAH BAGI PELAKSANAAN PEMBANGUNAN UNTUK KEPENTINGAN UMUM - Bustomi, Abuyazid (Solusi, 2018)
Land acquisition is any activity to obtain land by providing compensation to those who release or surrender land, buildings, plants, and objects related to land. Land acquisition can be carried out by the private sector and the government. In the case of land acquisition by the private sector, the methods carried out are through buying and selling, exchanging, or other means agreed upon by the parties concerned, which can be carried out directly between interested parties (for example: between developers with the right holder) with compensation for the amount or type determined in the deliberation. Whereas in the case of land acquisition by the government or regional government for the implementation of development in the public interest, it can be carried out by releasing or surrendering land rights, or also by revoking land rights through deliberation. Procurement of land for the implementation of development in the public interest is carried out through deliberation with the aim of obtaining an agreement on the implementation of development in the specified location, along with the form and amount of compensation. The deliberation process carried out by the land acquisition committee and the rights holder is intended to ensure that the rights holders receive adequate compensation for their land.